Thermodynamic Investigation of NaClO3 Solubility in the Mixed Solvent Medium and the Related Ion – Pair Formation at Different Temperatures - Aghaie, Mehran; Kishani, Roshanak (Journal of Applied Solution Chemistry and Modeling, 2015)
Using the evaporating method, the solubility of sodium chlorate was determined in the various mixed solvents (water + ethanol + propanol) at various temperatures. The results showed that the solubility of NaClO3 decreases with increasing the mass percent of ethanol and propanol. On the other hand, the solubility of NaClO3 increases with increasing the temperature. In addition, the equilibrium constant of ion pair formation, KIP, for the reaction Na+(aq) + ClO3-(aq) –>Na+ClO3- (Ion Pair) was estimated upon Fuoss contact ion pair model and then, the values of ion-pair concentrations were determined by using the extended Debye-Hückel model and iteration calculations in various mixed solvents and various temperatures . Finally the value of thermodynamic solubility product constant, Ksp(th), and the values ∆H°, ∆S° and ∆G° of ion-pair formation were estimated in the mixed solvent media.